Lipid Profile in Early and Late Stage among Patients with Nephrotic Syndrome-Related Chronic Kidney Disease in Dr. Hasan Sadikin General Hospital Bandung, Indonesia in 2016âˆ’2019 (Althea Medical Journal, 2023)
Background: Chronic kidney disease (CKD) is a major health problem in children with an increased prevalence globally. CKD is strongly associated with Nephrotic Syndrome (NS) and dyslipidemia, which become a progressive factor of CKD. This study aimed to describe the lipid profile of children with CKD and NS in Dr. Hasan Sadikin General Hospital Bandung, Indonesia.Methods: An observational-retrospective study was conducted with a cross-sectional design involving 150 medical records of children aged 1âˆ’18 years who were diagnosed with CKD with NS. Lipid profile data, including total cholesterol, triglycerides, LDL, and HDL, were collected from 2016âˆ’2019 using the total sampling method. Subjects with incomplete lipid profile data were excluded from the study.Results: Among the fifty-two children that were eligible and fulfilled the inclusion criteria, 88.5% were diagnosed with stage 1 CKD, and 32.7% were aged between 6âˆ’11 years and boys were predominant (67.3%). Lipid profile changes were found in the LDL, HDL, and total cholesterol serum levels between CKD stage I and II–V.Conclusions: Lipid profile of CKD pediatric patients with NS in Dr. Hasan Sadikin General Hospital Bandung in 2016âˆ’2019 showed hypertriglyceridemia and hypercholesterolemia. Most subjects were in stage I of CKD and Steroid-Resistant Nephrotic Syndrome, and comparison between stages of CKD and types of nephrotic syndrome is lacking. A prospective analytical study would be more reliable in proofing its significance.
Keywords: Chronic kidney disease; cholesterol; lipid profile; nephrotic syndrome; triglyceride